PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 2 PEMATANGSIANTAR - Oka Bagus Siahaan; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to gain knowledge regarding the influence of study habits and peer environment on learning outcomes in Class XI Economics subjects at SMA Negeri 2 Pematangsiantar. This research is of a quantitative type with the testing media used is SPSS 24. The sampling technique used a saturated sample of 106 students. The data collection technique used was a questionnaire. Instrument testing uses normality tests and reliability tests. The data analysis technique uses classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing, namely multiple linear regression analysis, t-test, f-test, and coefficient of determination.Data from research and management of partial test data (t-test) shows that the variable The variable Management of simultaneous test data (f-test) shows that F_count is 23.090 > F_table is 3.08, so it can be concluded that learning discipline and learning motivation have a positive and significant effect on student learning outcomes.